Pengaruh Kualitas Produk, Strategi Pemasaran Digital, dan Harga terhadap Keputusan Pembelian Konsumen di TikTok Shop pada FA Bucket Flowers - Indah Krisnawati; Christiawan Hendratmoko (JURNAL ILMIAH EDUNOMIKA, 2026)
The purpose of this study was to determine the extent to which product quality, digital marketing strategy, and price influence consumer purchasing decisions in the TikTok Shop on FA Bucket Flowers. This study used primary data from questionnaires and secondary data from literature studies. A total of 100 respondents served as the research sample, determined using a purposive sampling technique. The criteria were FA Bucket Flowers consumers who had made or planned to make a purchase through the TikTok Shop. The data analysis process was carried out through several stages, namely data instrument testing, classical assumption testing, and multiple linear regression analysis. The results showed that product quality did not significantly influence purchasing decisions, while digital marketing strategy and price were shown to significantly influence purchasing decisions in the TikTok Shop on FA Bucket Flowers. Based on these results, it is recommended that the company improve product quality, optimize promotions through the TikTok Shop feature, and maintain price consistency to maintain customer satisfaction and loyalty. For further research, it is recommended to consider additional variables such as consumer trust or brand image, and expand the research object beyond the TikTok Shop. Keywords: product quality, digital marketing strategy, price, purchasing decisions